Could Cardiac Shockwave Therapy be the Breakthrough Solution for Refractory Angina? A Systematic Review and Meta-Analysis - Pramesuari, Florentina Dewi; Aditya, Muhammad Reva; Mahbubi, Mustika (The Indonesian Heart Association, 2025)
Background: Refractory angina (RA) is a chronic condition unresponsive to standard treatments like PCI or CABG, leaving limited options for many patients. Cardiac shockwave therapy (CSWT) is a novel, noninvasive approach that enhances myocardial perfusion through microvascular regeneration. This systematic review and meta-analysis evaluate the effectiveness of CSWT in managing RA. Methods: A comprehensive literature search was conducted using electronic databases (Cochrane, PubMed, and ScienceDirect), including comparative studies with controls that evaluated CSWT in RA patients between 2010 and 2024. Studies not in English, with irrelevant outcomes, or lacking full-text access, were excluded. Data were extracted and analyzed using a random-effects model to address heterogeneity. Results: Seven studies, including 3 randomized controlled trials (RCTs) and 4 observational studies, with a total of 417 patients were analyzed. CSWT demonstrated significant improvements in multiple clinical outcomes. CSWT reduces angina severity in CSWT reduces angina severity in CCS grade (MD -0.76, 95% CI -0.97, -0.55, P < 0.00001) and in NYHA class (MD -0.62, 95% CI -0.95, -0.30, P = 0.0002), increased the 6- Minute Walk Test (6MWT) distance by 57.63 meters (MD 57.63, 95% CI 16.71, 98.54, P = 0.006), increased SAQ scores by 10.96 points (MD 10.96, 95% CI 1.66, 20.26, P = 0.02), improved LVEF by 4.43% (MD 4.43, 95% CI: 2.66 to 6.21, P< 0.01), and decreased nitroglycerin usage by 1.62 intake per week (MD -1.62, 95% CI -2.61, -0.62, P = 0.001). However, there was no significant difference in LVEDD between the two groups. Conclusion: CSWT appears to be a promising therapeutic option for patients with RA, demonstrating improvement in CCS angina class, NYHA class, 6-min walk test distances, SAQ score, LVEF, and reduces nitroglycerin usage. Keyword: Cardiac Shockwave Therapy, Refractory Angina, Non-invasive Cardiac Therapy, Chronic Angina Treatment, Innovative Angina Therapies